Measurement of Zinc Serum Level In Acute Myocardial Infarction Patients and Comparing With CKmb and Troponin - محمد دوران; محمد عماد خياط; باسم معروف (Latakia University Journal -Medical Sciences Series, 2024)
Background: Zinc is an important trace element that has been increasingly implicated in coronary artery disease. The study was designed to compare serum zinc levels in patients of coronary artery disease and healthy controls. Methods: It was a prospective, case control study. A total of 100 participants were divided into healthy controls (n = 50), Ischemic subjects with myocardial infarction (n = 50) were included in the study. The serum zinc was analyzed by atomic absorption spectrophotometry. Results: The mean age in the ischemic heart disease patients with infarction was comparable to the mean age of control group. Family history of ischemic heart disease and history of smoking were more common among disease as compared to controls. Serum zinc levels were found to be significantly low in study group (71.64) as compared to control group (104.90) and remaining study groups showed insignificant differences. Conclusion: Decreased serum zinc levels are associated with coronary artery disease especially the acute myocardial infarction.